English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

find the value of the equation?

2007-02-09 03:15:43 · 13 answers · asked by sarath v 1 in Science & Mathematics Mathematics

13 answers

Based on the information, it appears to be an exponentially growing infinite series, meaning that the answer is infinitely large. If you expand out the pieces, you can ignore all lower powers of x for purposes of inifinite series approximation. The total value, however, will be x^inf or x to the infinitieth power. So no limit is reached on this one...

2007-02-09 03:25:33 · answer #1 · answered by Tim 3 · 0 0

1] at X = 0 the X terms = 0 so f(0) = d = -2 2] f(1) = 5 = a+b+c+d so a+b+c = 7 3] f(-1) = 3 = -a+b-c+d ==> take out d ==> -a+b-c = 5 4] add "a+b+c = 7" and "-a+b-c = 5" to get 2b = 12 b=6 5] f(2) = 4 = 8a +4b + 2c +d plug in b = 6 and d = -2 4 = 8a + 24 + 2c -2 8a + 2c = -18 ===> 4a + c = -9 6] Subtract "-a+b-c = 5" from "a+b+c = 7" to get 2a + 2c = 2 a + c = 1 ==> c= 1 - a 7] substitute 6] into 5] get 4a + (1-a) = -9 simplify to 3a = -10 a = -10/3 8] c = 1-a = 1 - (- 10/3) = 1 + 10/3 = 13/3 = 4 1/3 The key test is that you had 4 unknowns [a, b, c, d] and four equations. With more unknowns or fewer equations you could not solve this.

2016-03-16 04:52:38 · answer #2 · answered by Megan 4 · 0 0

For the best answers, search on this site https://shorturl.im/avVky

put x= 0 f(x) = d = -2 put x = 1 f(x) = a + b+ c - 2 = 5 or a + b+ c = 7 put x= -1 f(-1) = -a + b-c - 2 = 3 or -a + b -c = 5 add the 2 above equation to get b = 6 and a + c = - 1 so f(x) =a x^3 + 5 x^2 +c x - 2 put x = 2 f(2) = 8a + 20 +2c -2 = 4 8a +2c = -14 2a + 2c = - 2 subtact to get 6a = - 16 a = -16/6 b =

2016-04-06 00:35:59 · answer #3 · answered by Anonymous · 0 0

Zero (0). As the series contains a term (x-x) which results in 0 the product becomes 0.

2007-02-09 03:24:19 · answer #4 · answered by raja 3 · 2 0

I think it isn't 0 because those two x's [in (x-x)] has different meanings. Think f(x) = (x-a)(x-b)(x-c)...(x-z) then first x means the x-axis value and the second x means a constant. So If you replace the second x with x_0 then f(x) is not 0 always. It's a polynomial with 27 terms and the highest power of x is 26.

2016-01-12 20:38:49 · answer #5 · answered by Eddie 1 · 0 0

zero
as it has x-x which is 0
0 X anything is zero

this is an old grade 4 joke

2007-02-09 03:26:42 · answer #6 · answered by varunchablani 2 · 0 0

It will be zero for obvious reasons. Give a sensible question next time.

2007-02-09 04:15:41 · answer #7 · answered by Shobiz 3 · 0 0

Zero.
This is a very easy question as u can find from so many right answers.

2007-02-09 16:10:44 · answer #8 · answered by Bishu 3 · 0 0

0 (zero)
the equation contains (x-x) which will result the entire expression in 0.

2007-02-11 17:36:47 · answer #9 · answered by Delhi Prince 1 · 0 0

answer is zero because this expresion will contain
a term (x-x) which is equal to zero i have already answered it before

2007-02-09 03:26:03 · answer #10 · answered by Anonymous · 0 0

fedest.com, questions and answers